A visual test for a unit root: Geary's count of sign changes revisited - Honohan, Patrick; Geary, R. C. (Economic & Social Studies, 1996)
Prompted by Geary's (1970) suggestion in a different context, the stationarity of a plotted time series can be assessed by simply counting the number of times the plot crosses the trend line linking the first and last observations. The 95 per cent critical value is conveniently approximated by twice the square root of the sample size. Despite its simplicity, the test has surprisingly good power.
Keywords: Unit roots; Count of sign; Statistical methods